MODEL PEMBERDAYAAN EKONOMI KELUARGA MISKIN TERINTEGRASI DENGAN WIRAUSAHA PRODUK IKAN - - Marwanti; Siti Hamidah; - Yuriani (LPPM UNY, 2014)
This study aims to: (1) ind economic and noneconomic issues that constrain poor families in the region Kretek Bantul, Yogyakarta; (2) ind a way to develop models of economic empowerment of poor families is integrated with entrepreneurial ish products so as to improve the entrepreneurial attitude and skills of families in Kretek Bantul; and (3) produce models of empowerment of poor families in the form of guide books and learning tools that are practical to implement. This study uses qualitative and quantitative approaches. Development of a model using the approach R D from Borg Gall summarized into 3 construct a model: a preliminary study,development models, and testing models, which are arranged in two stages. The irst stage, in economic and noneconomic issues that constrain poor ishing families, inding ways of economic empowerment of poor families, and result in the model of economic empowerment of poor families in the form of guide books and learning tools. The second phase in the form of implementation models and socialization models in a broader scope